Immunodomination of Serotype-Specific CD4+ T-Cell Epitopes Contributed to the Biased Immune Responses Induced by a Tetravalent Measles-Vectored Dengue Vaccine - Lin, Tsung-Han; Chen, Hsin-Wei; Hsiao, Yu-Ju; Yan, Jia-Ying; Chiang, Chen-Yi; Chen, Mei-Yu; Hu, Hui-Mei; Wu, Szu-Hsien; Pan, Chien-Hsiung (Frontiers in Immunology, 2020)
engue is an emerging mosquito-borne disease, and the use of prophylactic vaccines is still limited. We previously developed a tetravalent dengue vaccine (rMV-TDV) by a recombinant measles virus (MV) vector expressing envelope protein domain III (ED3). In this study, we used dengue-susceptible AG129 mice to evaluate the protective and/or pathogenic immune responses induced by rMV-TDV. Consistent with the previous study, rMV-TDV-immunized mice developed a significant neutralizing antibody response against all serotypes of DENV, as well as a significant IFN-γ response biased to DENV-3, compared to the vector controls. We further demonstrated that this DENV-3-specific IFN-γ response was dominated by one CD4+ T-cell epitope located in E349-363. After DENV-2 challenge, rMV-TDV-immunized mice showed a significantly lower viremia and no inflammatory cytokine increase compared to the vector controls, which had an ~100 times higher viremia and a significant increase in IFN-γ and TNF-α. As a correlate of protection, a robust memory IFN-γ response specific to DENV-2 was boosted in rMV-TDV-immunized mice after challenge. This result suggested that pre-existing DENV-3-dominated T-cell responses did not cross-react, but a DENV-2-specific IFN-γ response, which was undetectable during immunization, was recalled. Interestingly, this recalled T-cell response recognized the epitope in the same position as the E349-363 but in the DENV-2 serotype. This result suggested that immunodomination occurred in the CD4+ T-cell epitopes between dengue serotypes after rMV-TDV vaccination and resulted in a DENV-3-dominated CD4+ T-cell response. Although the significant increase in IgG against both DENV-2 and -3 suggested that cross-reactive antibody responses were boosted, the increased neutralizing antibodies and IgG avidity still remained DENV-2 specific, consistent with the serotype-specific T cell response post challenge. Our data reveal that immunodomination caused a biased T-cell response to one of the dengue serotypes after tetravalent dengue vaccination and highlight the roles of cross-reactive T cells in dengue protection.